2018
DOI: 10.1021/acs.est.7b04668
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Photodegradation of Polybrominated Diphenyl Ethers in Car Seat Fabrics from End-of-Life Vehicles

Abstract: In this study, we examined the photodegradation of decabromodiphenyl ether (BDE-209) on the surface of car seat covers from end-of-life vehicles (ELVs). Samples were collected at two car dismantling facilities in Sweden and cover car models from 1989 to 1998. The content of polybrominated diphenyl ethers (PBDEs) in nine real samples (fabric and polyurethane foam) was first characterized. Fabric samples that did not contain BDE-209 were then spiked with BDE-209 and irradiated in the laboratory and under sunligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 47 publications
(89 reference statements)
0
18
1
Order By: Relevance
“…Surprisingly, these values are much higher than those found in THF. In a previous study, we have shown that BDE-209 exhibits very high photoreactivity in PS compared to other polymers such as PET and cellulose (Khaled et al, 2018). While the reasons for this high photoreactivity in PS are not clear, several assumptions can be postulated:…”
Section: Quantum Yields Of Photodegradationmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, these values are much higher than those found in THF. In a previous study, we have shown that BDE-209 exhibits very high photoreactivity in PS compared to other polymers such as PET and cellulose (Khaled et al, 2018). While the reasons for this high photoreactivity in PS are not clear, several assumptions can be postulated:…”
Section: Quantum Yields Of Photodegradationmentioning
confidence: 99%
“…-a higher hydrogen donor capacity of PS which can promote debromination and thus accelerate photodegradation (Kajiwara et al, 2008;Khaled et al, 2018). This can be explained by the lower C-H bond dissociation energy in PS or Ar-C-H (386 kJ/mol) than in THF (410 kJ/mol) (Agapito et al, 2005).…”
Section: Quantum Yields Of Photodegradationmentioning
confidence: 99%
See 1 more Smart Citation
“…After the 10, 20 and 30 days, the HCHO pollution decrease by 34.1%, 56.9% and 73.6%, respectively. For the HCHO and VOCs pollution mainly comes from cabin indoor materials including leather trims, organic solvents, paints, adhesives and so on [11][12][13]25 . In contrast with old vehicles, new vehicles have the newer materials with the stronger HCHO emissions, which lead to the higher HCHO pollution.…”
Section: Resultsmentioning
confidence: 99%
“…The possible intermediates that were measured included lower brominated products, hydroxylated BDEs, bromophenols, brominated and hydroxylated dibenzofurans (PBDFs) and dioxins (PBDDs). An accelerated degradation might be explained by the H-donor capacity of water which can promote debromination as well as hydroxylation [20]. Thus, a significant number of electrons was required for the sequential reductive reactions of BDE-209 by photolysis in a sorbent/water system.…”
Section: Influence Of Uv Irradiation On Bde-209 Degradation In a Claymentioning
confidence: 99%